Role of coconut shell biochar and earthworm (Eudrilus euginea) in bioremediation and palak spinach (Spinacia oleracea L.) growth in cadmium-contaminated soil. (15th January 2022) - Noronha, Florence Ruth; Manikandan, Soumya Koippully; Nair, Vaishakh
Abstract: The contamination of soil with heavy metals is known to affect the yield the soil fertility, which in turn affects the growth of agricultural crops. This study investigates the role of coconut shell biochar (CSB) and earthworms ( Eudrilus euginea ) in the bioremediation and growth of Palak spinach ( Spinacia oleracea L.) in cadmium (Cd) contaminated soil. The soils were amended with different combinations of CSB and earthworms and incubated for 35 days. Later, the soil samples were analyzed for the changes in the soil properties, soil enzyme activity, and heavy metal contents. It is observed that the treatments with both CSB and earthworms resulted in the improvement of soil properties and soil enzyme activity which was directly related to soil fertility. Meanwhile, the maximum removal of 94.38% of total Cd content in the soil was obtained for the soil sample contain both CSB and earthworms. The improved soil properties resulted in a higher germination percentage of Spinacia oleracea L. seeds in the Cd contaminated soil. Graphical abstract: Image 1 Highlights: First work to report the use of earthworm ( Eudrilus euginea ) with biochar for Cd removal and plant growth studies in soil. Addition of both biochar and earthworms together resulted in the decrease of total Cd and bioavailable Cd. Increase in the enzyme activity is observed in the biochar-earthworm treated contaminated soil. Use of biochar and earthworm enhanced plant growth by increasing soil fertility.